Associations between PM2.5, ambient heat exposure and congenital hydronephrosis in southeastern China - Huang, ZhiMeng; Zhong, XiaoHong; Shen, Tong; Gu, SongLei; Chen, MengNan; Xu, WenLi; Chen, RuiQi; Wu, JinZhun; Yang, XiaoQing (Frontiers in Public Health, 2024)
Whether the occurrence of congenital hydronephrosis(CH) is affected by fine particulate matter (PM2.5) and ambient heat exposure during pregnancy.A case-control study was conducted to investigate the relationship between exposure to PM2.5, ambient heat exposure and CH during pregnancy. We included 409 case groups and 409 control groups from 2015 to 2020. By using spatial remote sensing technology to monitor PM2.5 concentration, PM2.5 and ambient temperature exposure were assigned to each participant.The logistics regression model was used to calculate the influence of PM2.5 and ambient heat exposure on CH. Stratified analysis and interaction analysis were used to study the interaction between ambient heat exposure and PM2.5 on the occurrence of CH.At 6 th week of gestation, PM2.5 may increase the risk of CH. For every 10ug/m 3 increase in PM2.5 exposure, the risk of CH increased by 2% (95%CI=0.98,1.05), but P>0.05, indicating that there was no significant relationship between the results. Exposure to intense heat exposure at 6 th and 7 th week of gestation increased the risk of CH. For every 1°C increase in heat exposure, the risk of CH in offspring increased by 21% (95%CI=1.04,1.41) and 13% (95%CI=1.02,1.24), respectively. At 5 th week and 6 th week of gestation, the relative excess risk due to interaction (RERI) was greater than 0 at the 50 th percentile (22.58°C), 75 th percentile (27.25°C), and 90 th percentile (29.13°C) of daily maximum temperature (Tmax) distribution, indicating that the risk of CH was higher than that of single risk factor when exposed to ambient heat exposure and PM2.5 at the same time.Exposure to PM2.5 and ambient heat exposure during pregnancy increases the risk of CH. There was a positive interaction between exposure to intense heat exposure and high concentration of PM2.5 on the occurrence of CH. Keyword： congenital hydronephrosis, heat exposure, PM2.5, China